Game of stars - DasGupta, Sayantani; To, Vivienne (New York : Scholastic Press, 2019)
Months after Kiranmala's adventure in the Kingdom Beyond, a vision of the Demon Queen starts showing up in her bedroom, trying to tell Kiran something, but getting cutoff before she can finish; then she starts seeing an advertisement for an archery contest on her family's interdimensional television and Kiran realizes that she must return to her place of birth--where society is falling apart, a reality show is taking over, her friends are in danger, and she, once again, becomes the warrior princess she was meant to be.
School Library Journal starred, December 2018
Kirkus Starred, October 2018
Booklist, December 2018
5.0
3-6
830L
Keywords: East Indian Americans -- Juvenile fiction; Princesses -- Juvenile fiction; Magic -- Juvenile fiction; Quests (Expeditions) -- Juvenile fiction; Adventure stories; East Indian Americans -- Fiction; Princesses -- Fiction; Magic -- Fiction; Quests (Expeditions) -- Fiction; Adventure and adventurers -- Fiction; Fantasy; Fantasy fiction; Action and adventure fiction